2019
DOI: 10.1093/cid/ciz032
|View full text |Cite
|
Sign up to set email alerts
|

Extended Infusion of β-Lactams for Bloodstream Infection in Patients With Liver Cirrhosis: An Observational Multicenter Study

Abstract: Background We analyzed the impact of continuous/extended infusion (C/EI) vs intermittent infusion of piperacillin-tazobactam (TZP) and carbapenems on 30-day mortality of patients with liver cirrhosis and bloodstream infection (BSI). Methods The BICRHOME study was a prospective, multicenter study that enrolled 312 cirrhotic patients with BSI. In this secondary analysis, we selected patients receiving TZP or carbapenems as adeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…Moreover, two recent meta-analyses have shown an association between prolonged infusion of BLA and lower mortality rates [10,11]. Similar results have also been observed in a non-randomised prospective study in cirrhotic patients with bloodstream infections, in whom prolonged infusion of BLA was associated with improved survival [12]. Nevertheless, earlier studies addressing this issue have mainly focussed on the general non-severely immunocompromised population.…”
Section: Introductionsupporting
confidence: 66%
“…Moreover, two recent meta-analyses have shown an association between prolonged infusion of BLA and lower mortality rates [10,11]. Similar results have also been observed in a non-randomised prospective study in cirrhotic patients with bloodstream infections, in whom prolonged infusion of BLA was associated with improved survival [12]. Nevertheless, earlier studies addressing this issue have mainly focussed on the general non-severely immunocompromised population.…”
Section: Introductionsupporting
confidence: 66%
“…This was a multicentre caseecontrolecontrol (1:2:2) study performed in four Italian tertiary centres over a 10-year study period (from January 2006 to December 2015). Patients were selected from prospective collected databases used for other purposes [13,14]. The study was approved by the Institutional Review Boards of participating study sites.…”
Section: Methodsmentioning
confidence: 99%
“…12,53,83 A recent prospective multicentre study in patients with cirrhosis and BSI showed that a loading dose followed by continuous infusion of b-lactams improves 30-day survival compared to traditional dosing schedules. 84 Most high-dose antibiotic strategies are off label and their safety profile needs to be proven in patients with cirrhosis.…”
Section: Key Pointsmentioning
confidence: 99%